Analisis Penggunaan Sistem Informasi Kesehatan Terhadap Kepuasaan Pelayanan Medis Di Puskesmas Bambu - Nur istiqamah D; Anisa Aulia; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
The development of information technology in the healthcare sector has encouraged healtcare facilities to adopt health information systems (HIS) to improve operational efficiency, data accuracy, and the quality of medical services. Puskesmas Bambu, as a primary healthcare facility, has implemented HIS in various service aspects, including patient registration, electronic medical record management, queuing systems, and management reporting. However, it is important to evaluate the extent to which this system meets information needs and provides a positive impact on patient satisfaction. This study aims to analyze the effect of health informatioan system utilization on the level of medical service satisfaction using a descriptive quantitative approach. Data were collected through observations, of service processes, documentation review, and the distribution of questionnaires to patients and healthcare personnel involved in the use of the HIS. The results indicate that the implementation of the HIS significantly acclererates administrative processes,improves the accuracy of information, and simplifies service workflows. Patients reported improvements in service spead, clarity of medical information, queue convenience, and the professionalism of healthcare staff. Correlation analysis also revealed a positive of HIS utilization and the level of medical service satisfaction. These findings confirm that optimizing the utilization of health information systems can serve as a key strategy for improving healthcare service quality and patient satisfaction at Puskkesmas Bambu. Furthermore, this study is expected to serva as a reference for policymakers in developing more efficient and sustainable healthcare information technology systems.